Rancang Bangun Aplikasi Memprediksi Penggunaan Infus di Rumah Sakit menggunakan Metode Moving Average (Studi Kasus Rumah Sakit Arun Lhokseumawe) - Phonna, Riezqya Arrina; Mahdi, Mahdi; Azhar, Azhar (Jurnal Teknologi Rekayasa Informasi dan Komputer, 2022)
Hospital is a health service institution that provides complete health services. The better the health service, the more satisfied the patient will be, and vice versa. In this study, we will discuss the availability of infusion fluids for patients in optimal amounts. Hospitals must provide Infusion supplies for patients for a period of 1 period or 1 month. So far, planning for Infusion requests for use in the next period, is still using instinctive techniques by the head of the hospital warehouse. Thus, this will result in an excess or even a decrease in the Infusion supply. Thus, this problem can be solved by predicting the need for Infusion in the future period for the need for Infusion for the patient. In this study, we will build a system that is able to predict future Infusion needs. The results of this prediction can be used as a reference in planning for Infusion requests to the health office. The purpose of this research is to be able to build a prediction system for future Infusion inventory needs in hospitals using the Moving Average method. Thus, this system can assist the planning process of future drug needs in hospitals. Moving Average is an indicator that calculates the average price of an asset over a certain period of time, then connects it in the form of a line. The average value is calculated based on 3 periods, one period of 30 days or 1 month. The Moving Average (MA) method uses the average of the last few data as forecast data for the next future. The result of this study is a prediction system, which is able to predict the use of infusion needs in the future. The test of this system includes an error accuracy of 26.54% based on testing 8 data scenarios. Keywords — Infusion, Moving Average, Prediction, Hospital.